Chromosomal mapping and expression of the human cyr61 gene in tumour cells from the nervous system. Issue 6 (December 1997) - Martinerie, C; Viegas-Pequignot, E; Nguyen, V C; Perbal, B
Abstract : AIMS: To characterise the human cyr61 gene (cyr61H) and determine its chromosomal locality. To compare expression of cyr61H in human tumour cell lines with that of two other structurally related genes, novH (nephroblastoma overexpressed gene) and CTGF (connective tissue growth factor), that are likely to play a role in the control of cell proliferation and differentiation. METHODS: To isolate the human cyr61 gene, placental genomic and HeLa cDNA libraries were screened with murine cyr61 cDNA. The nucleotide sequence of the complete cyr61H cDNA was established. Both Southern blotting of a panel of somatic cell hybrids and in situ hybridisation on chromosomes were performed to map the cyr61H gene. Expression of cyr61H, novH, CTGF, and novH was analysed by northern blotting in both human neuroblastomas and glioblastoma cell lines. RESULTS: Genomic and cDNA clones encompassing the cyr61H gene were isolated and characterised. Comparison of mouse and human cyr61 sequences indicated that their genomic organisation is highly conserved. Alignment of coding sequences highlighted the conservation of cyr61 regions that might be critical for its biological function. The data showed that the cyr61H gene is assigned to chromosome 1p22.3 and that different levels of cyr61H, CTGF, and novH mRNA have been detected in several human tumour cell lines derived from the nervous system. CONCLUSIONS: The human cyr61 gene belongs to an emerging family of genes including CTGF/fisp12 and nov. The murine cyr61 encodes an extracellular cysteine rich protein that exhibits chemotactic activity, promotes attachment and spreading of cells, and potentiates the mitogenic effect of growth factors. Assignment of the cyr61H gene to chromosome 1p22.3 will allow studies to determine whether human pathologies derived from the nervous system or from other tissues are associated with chromosomal abnormalities involving this region. Although the coding regions of cyr61H, CTGF, and novH are highly homologous, a growing body of evidence suggests that expression of these genes is regulated differentially, and that a balance between expression of these genes might represent a key element in determining the stage of differentiation and/or the malignant potential of tumour cells.